Монетное обращение Керкинитиды V-III вв. до н.э. - Кутайсов, В.А. (Материалы по археологии, истории и этнографии Таврии, 2002)
Monetary circulation in Kerkinitis during the period of the 4th - 2nd centuries BC are examined in this article.